CDH1, a Novel Surface Marker of Spermatogonial Stem Cells in Sheep Testis - Yan ZHANG; Sachula WU; Fen-hua LUO; Baiyinbatu; Lin-hong LIU; Tian-yuan HU; Boyang YU; Guang-peng LI; Ying-ji WU (Journal of Integrative Agriculture, 2014)
Spermatogonial stem cells (SSCs) are unique stem cells in adult body that can transmit genetic information to the next generation. They have self-renewal potential and can continuously support spermatogenesis throughout life of a male animal. However, the SSC population is extremely small, isolation and purification of the SSCs is challenging, especially for livestock animals. It has been confirmed that CDH1 (cadherin-1, also known as E-cadherin) can be expressed in undifferentiated SSCs of mouse and rats, but it has not been verified in sheep. Here, CDH1 was found as a novel surface marker for sheep SSCs. In this paper, sheep anti-CDH1 polyclonal antibodies were prepared and its activity was checked. Using the obtained antibodies and immunohistochemistry analysis, we confirmed that CDH1 can be expressed by SSCs in sheep testis.